(untitled) (Web of Teachers: Inderscience Research, 2025)
In the context of the modernization of the agrarian sector of the Republic of Uzbekistan, the issue of adapting foreign experience in agricultural taxation is becoming relevant. The article considers the main models used in world practice, including cadastral and profit systems, as well as environmental and investment incentives. The possibilities of their application in Uzbekistan are determined taking into account local specifics: the dominance of the state sector, limited access of small farms to benefits, and the need for institutional reforms. Keywords: agriculture, taxation, foreign experience, tax incentives, agro-industrial complex, Uzbekistan, tax reform, digitalization.